Recreational Language Learning: Exploring English Expressions Found in Ika Natassa’s Novel - Niswatin Nurul Hidayati (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
Many ways that can be used to learn English, including with recreational language learning. Thus, the process of learning a foreign language is not only in the classroom in a formal nuance, but also in done through fun things. One of them is by reading a novel. The purpose of this research was to describe and explore English expressions in novels written by Ika Natassa. These novels are interesting to study because they are written by Indonesian woman in Indonesian. However, there are quite a lot of English expressions inside it. With this phenomenon, readers will indirectly learn foreign languages in a fun way. Then, with the context written in the novel, the reader will understand the meaning without needing to open the dictionary or interpret it word for word. This research used descriptive qualitative method. From observations that have been made, found some vocabulary and expressions with the theme of traveling, the world of banking, formal expressions and slang in English.